Identification of Enablers and Inhibitors of Supply Chain Managementin Indian Hospital - Mr. Shashank Srivastava (International Journal of Advanced Science and Technology, 2020)
Management of hospital supply chain is a critical issue as it relates the survival of the humanbeings. Serving the patient at minimum costis the objective of hospitalsupplychain management. Hospital are the main entitywhere the treatmentisprovided to the patient. Thereforeitis essential that its supply chain thoroughly understood and properly managed. This researchpaper serve thispurpose and shows the problems, enablers and inhibitors of hospitalsupplychain management. Various techniques also have been discussed in brief in order to improve the performance of the chain. This willhelpful to the decision maker in order to improve the patient care at minimum possible cost.